Understanding divergent academic outcomes: English learning students' success and struggles after transitioning to all-English instruction - Montes, Alexandra (My University, 2026)
This qualitative case study explored how bilingual and ESL teachers' beliefs, knowledge, and attitudes shape the implementation of bilingual programs and students' experiences as they transition from bilingual education to all-English instructional settings in Texas. Despite the cognitive and academic advantages associated with bilingualism, research shows that many ELs experience significant setbacks after this transition, even when previously identified as high-achieving or gifted and talented. Grounded in theories of second-language acquisition and language orientation, this study examined how bilingual and ESL teachers' knowledge, beliefs, and attitudes influence program implementation and shape students' transition experiences. Data was collected through semi-structured interviews and focus groups from an urban elementary school with a high concentration of ELs. Thematic analysis identified patterns related to instructional practice, teacher perceptions, and transitional supports. Findings contribute to the literature on bilingual education by highlighting how teacher beliefs and program implementation shape students' transition experiences and influence their engagement with academic language demands post-transition. These insights offer implications for educators and policymakers aiming to enhance outcomes for ELs in high-immigrant, high-poverty communities. The study holds particular significance considering growing EL enrollment in the targeted southern state, expanding accountability systems, and persistent achievement gaps linked to program fidelity and teacher expectations. Results will inform more equitable and context-responsive approaches to bilingual education and EL support.
Keywords: Bilingual education; Bilingual teacher; English language learner; English limited; Dual language; ESL programs; Value added